IMPLEMENTATION OF E-MODULES IN PRIMARY SCHOOL STUDENT LEARNING: A SYSTEMATIC LITERATURE - Kiky Rosita Dewi; Tri Joko Raharjo; Harianingsih Harianingsih; Bambang Subali; Nuni Widiarti (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
This research aims to identify and analyze the application of e-modules in primary education and evaluate their effectiveness in improving student learning outcomes. The method used is Systematic Literature Review (SLR), which involves collecting and analyzing articles published between 2020 and 2025 related to the use of e-modules in primary schools. The research data was collected from various credible academic database sources, including Google Scholar, SINTA, DOAJ, ResearchGate, and Scopus resulting in 27 relevant articles for analysis. The results showed that the application of e-modules is very effective in increasing students' learning motivation, improving material understanding, and developing critical thinking skills. Technology-based e-modules, such as flipbooks and blended learning models, can increase interactivity in learning and make it easier for students to learn independently. In addition, the integration of local wisdom and character values in e-modules plays an important role in student character building. E-modules are an effective solution to the challenges of education in the digital era. Its application in elementary schools can improve the quality of learning, provide an interesting learning experience, and support the implementation of the Merdeka curriculum. Therefore, the development and wider application of e-modules is highly recommended to support the learning process in primary schools. Keywords: Learning Media, E-Module, Elementary School